Investigation of Initial Viral Loads and Patient Characteristics as Predictors of COVID-19 Outcomes: A Retrospective Cohort Study - Elfira Yusri; Syandrez Prima Putra; Liganda Endo Mahata; Andani Eka Putra (MDPI AG, 2023)
Limited evidence exists on whether initial viral load and patient characteristics can predict unfavorable outcomes in future outbreaks of coronavirus disease 2019 (COVID-19). This retrospective cohort study examined the relationship between the initial viral load, patient characteristics, and outcomes during the second-wave COVID-19 outbreak in West Sumatra, Indonesia. We analyzed the COVID-19 patients admitted to a secondary hospital between the 1 June 2021 and the 31 August 2021. The initial viral load was determined using the real-time quantitative-polymerase chain reaction (RT-qPCR) cycle threshold (Ct) value, categorized as low (LIVL, Ct > 20) or high (HIVL, Ct ≤ 20). Multivariate logistic regression was used to assess the relationship between the initial viral load, age, sex, vaccination status, comorbidities, and outcomes, including disease severity, hospital stay length, ICU admission, invasive ventilation, and in-hospital mortality. Receiver operating characteristic (ROC) curves and the area under the curve (AUC) were used to assess the diagnostic performance of the initial Ct values in predicting COVID-19 outcomes. The study included 373 patients (median age [range]: 48 [0-94]; male: 40.21%; HIVL: 34.85%; unvaccinated: 86.06%; comorbidities: 52.01%). The HIVL patients significantly had a lower risk of developing severe/critical outcomes (OR: 0.506; 95% CI: 0.310-0.825; p = 0.006) and needing invasive ventilation (OR: 0.290; CI: 0.098-0.854; p = 0.025). The Ct value used to indicate severe/critical outcomes was 23.57. More severe outcomes were significantly observed in LIVL patients, those aged >60 years, males, unvaccinated individuals, and those with comorbidities. This study emphasizes the importance of primary prevention, early screening, and immediate care for COVID-19 in saving lives.